Deepening, Broadening, and Charting: Extending the Reach and Impact of Evidence‐Based Practices for Leadership Development. Issue 168 (30th November 2020) - Johnson, Matthew R.; Soria, Krista M.
Abstract: In this chapter, the authors synthesize key ideas presented by authors in this issue to leverage evidence‐based practice in curricular and co‐curricular leadership development. Additionally, they offer guidance for deepening the impact of these practices and broadening their effects to other groups. Lastly, they chart directions for future research on evidence‐based practices.